Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian Ulang Melalui Kepuasan Konsumen Sebagai Variabel Intervening pada Minuman Yotta di Cabang Tinumbu - Ayu Sulistiya Putri Syahrir; Agung Widhi Kurniawan; Muhammad Ilham Wardhana Haeruddin; Muhammad Ichwan Musa; Zainal Ruma (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this study is to determine the effect of service quality and product quality variables on repurchase decisions through consumer satisfaction as an intervening variable. This research employs a quantitative approach utilizing primary data obtained through questionnaires from respondents. The population in this study consists of 1,380 consumers of Yotta Tinumbu Branch, Makassar City, based on sales data from August to December. The sample in this study was selected using Hair's method, with a total of 150 respondents. The analysis method is conducted using SEM-PLS. The results of this study show that service quality and product quality have a positive and significant impact on consumer satisfaction at Yotta Tinumbu branch. Furthermore, consumer satisfaction also has a positive and significant impact on repurchase decisions. Service quality directly affects repurchase decisions, while product quality does not have a significant impact on repurchase decisions. Additionally, service quality influences repurchase decisions through consumer satisfaction as an intervening variable, whereas product quality does not have a significant impact through this variable.